FINANCIAL PERFORMANCE DETERMINANTS MODERATED BY COMPANY SIZE: THE CASE OF PALM OIL PLANTATION SUB-SECTOR IN INDONESIA - Susilo, Inderijati; Kurniasih , Augustina (IJOSMAS, 2025)
This study aims to analyze the effects of Crude Palm Oil Price (CPOP), Corporate Social Responsibility(CSR), Leverage (DER), and Enterprise Risk Management Disclosure (ERMD) on corporate financialperformance (ROA), with Firm Size as a moderating variable. Employing a quantitative approach, the studyutilized data from a population of 28 palm oil plantation companies listed on the Indonesia Stock Exchange (IDX)in 2024. Using a purposive sampling technique, the research sample consisted of 15 companies that met thecriteria of publishing a sustainability report during the 2019-2023 period. The regression results indicate thatCPOP, CSR, and ERMD have no significant effect on ROA. However, DER was found to have a significantnegative effect on financial performance. Furthermore, the moderation analysis reveals that Firm Sizesignificantly and positively moderates the effect of DER on ROA. These findings suggest that while high debt cangenerally be a burden, larger firms possess the ability to manage leverage effectively, turning it into a driver offinancial performance.